The Relationship Between Nutritional Knowledge and Attitudes and Energy Adequacy Levels Among Futsal Club Members (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2026)
Futsal is a high-intensity sport that requires adequate energy intake to support training performance, recovery, and overall athletic development. Nutritional knowledge and nutritional attitudes are considered important factors influencing dietary behavior and energy adequacy among adolescent athletes. However, the extent to which these factors are associated with energy adequacy levels among school-based futsal players remains unclear. Therefore, this study aimed to determine the relationship between nutritional knowledge and nutritional attitudes with energy adequacy levels among members of the SMAN 2 Makassar futsal club. This study employed a quantitative approach with a cross-sectional design. The population consisted of all members of the SMAN 2 Makassar futsal club, totaling 40 athletes, with 37 respondents meeting the study criteria and participating in data collection. Data were obtained using a nutritional knowledge questionnaire, a nutritional attitude questionnaire, and a two-day 24-hour food recall to assess energy intake. Data analysis was performed using the Fisher Exact test with IBM SPSS version 22. The results showed that most respondents had moderate nutritional knowledge (45.9%) and moderate nutritional attitudes (56.8%). Regarding energy adequacy, 51.4% of respondents were classified as having low energy adequacy levels, while 48.6% had adequate energy intake. Statistical analysis revealed no significant relationship between nutritional knowledge and energy adequacy levels (p = 0.306), as well as no significant relationship between nutritional attitudes and energy adequacy levels (p = 0.838). In conclusion, nutritional knowledge and nutritional attitudes were not significantly associated with energy adequacy levels among futsal club members at SMAN 2 Makassar. These findings suggest that factors beyond knowledge and attitudes, such as eating habits, food availability, lifestyle, and training schedules, may play a more substantial role in determining energy adequacy among adolescent athletes.